2011
DOI: 10.1111/j.1365-2788.2011.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of life in families with children who have intellectual and developmental disabilities in Slovenia

Abstract: The family members rated Importance high for all of the quality of family life domains, but it appears from the lower Opportunities scores that their opportunities are limited; this may result in fewer possibilities for attaining a better quality of life. The results of our research are useful to Slovene researchers who work in the areas of special pedagogy and rehabilitation, politicians, non-governmental organisations and social services. The quality of life of families with children with disabilities, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
5
16
0
9
Order By: Relevance
“…This study found that the highest perception of satisfaction was in the Family Interaction domain, which is supported by several other studies (BalcellsBalcells et al, 2010;Park, 2001;Clark et al, 2011;Cagran et al, 2011;Brown et al, 2003;Brown, Petrowski, et al, 2010;Jokinen, 2008). The lowest satisfaction was in the domain of Physical/Material WellBeing, which is also supported by several other studies (Tang et al, 2005;Clark et al, 2011;Cagran et al, 2011;Svraka et al, 2011). Likely, it was the financial struggle of Turkish families who have children with ID and autism that caused families in this study to have lower perceptions of satisfaction with Physical/Material WellBeing, as compared to other domains.…”
Section: Summary Of Major Results and Connectionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study found that the highest perception of satisfaction was in the Family Interaction domain, which is supported by several other studies (BalcellsBalcells et al, 2010;Park, 2001;Clark et al, 2011;Cagran et al, 2011;Brown et al, 2003;Brown, Petrowski, et al, 2010;Jokinen, 2008). The lowest satisfaction was in the domain of Physical/Material WellBeing, which is also supported by several other studies (Tang et al, 2005;Clark et al, 2011;Cagran et al, 2011;Svraka et al, 2011). Likely, it was the financial struggle of Turkish families who have children with ID and autism that caused families in this study to have lower perceptions of satisfaction with Physical/Material WellBeing, as compared to other domains.…”
Section: Summary Of Major Results and Connectionsupporting
confidence: 89%
“…Regarding domains, a consistent finding across studies has been the highest FQOL score for the domain of Family Relationships (Brown, Anand, Isaacs, Baum, & Fung, 2003;Brown, Petrowski, et al, 2010;Cagran, Schmidt, & Brown, 2011;Clark, Brown, & Karrapaya, 2011) based on data from Canada, Malaysia, and Slovenia. A consistent pattern across Canada, Korea, Malaysia, and Bosnia-Herzegovima data has been the finding of the Financial/Physical/Material Well-Being domain having the lowest FQOL score (Cagran et al, 2011;Clark et al, 2011;Svraka et al, 2011;Tang et al, 2005). Two additional domains receiving low scores are Receiving Support From Others and Receiving DisabilityRelated Services (Brown, Petrowski, et al, 2010;Brown et al, 2003).…”
mentioning
confidence: 86%
“…Dez dos estudos apresentados tiveram como objetivo a validação da referida escala nos seguintes países: Bósnia-Herzegovina (Svraka, Loga & Brown, 2011), Bélgica (Steel, Poppe, Vandevelde, Van Hove, & Claes, 2011), Itália (Bertelli, Bianco, Rossi, Scuticchio, & Brown, 2011), Eslovénia (Čagran, Schmidt, & Brown, 2011), Israel (Neikrug, Roth, & Judes, 2011), Malásia (Clark, Brown, & Karrapaya, 2012), Nigéria (Ajuwon & Brown, 2012), Austrália (Rillotta, Kirby, Shearer, & Nettelbeck, 2012), EUA (Samuel, Hobden, LeRoy, & Lacey, 2012) e Polónia (Ho et al 2013). Em todos esses estudos, recorreuse ao FQOLS-2006, com algumas especificações, quer na metodologia, quer na análise dos resultados, que se descrevem seguidamente.…”
Section: Artigos Empíricos Com Base No Fqols-2006unclassified
“…Em alguns estudos, apresentam-se correlações entre dimensões e entre domínios (Bertelli et al, 2011), entre domínios para cada dimensão (Clark et al, 2012) e apenas entre dimensões (Ajuwon & Brown, 2012). Existe, também, uma preocupação em complementar os dados quantitativos com informação de natureza qualitativa, quer seja através dos dados recolhidos com o questionário (Čagran et al, 2011;Ajuwon & Brown, 2012;Rillotta et al, 2012), quer através de uma entrevista (Steel et al, 2011). Apenas um dos estudos anteriormente referidos apresenta os índices de consistência interna , sendo os valores do coeficiente alfa de Cronbach baixos a moderados (Importância = 0,24; Realização = 0,69; Oportunidades = 0,79; Estabilidade = 0,45; Satisfação = 0,82; Iniciativa = 0,48).…”
Section: Artigos Empíricos Com Base No Fqols-2006unclassified
“…El peregrinaje en busca de un diagnóstico fiable es una etapa difícil de superar, no sólo porque en ocasiones puede durar mucho tiempo sino por el desgaste físico, psicológico y emocional que genera en los padres; es importante que éstos tengan el diagnóstico de su hijo lo antes posible, ya que conocerlo puede ser el principio de la aceptación de su realidad y de permitirse comenzar a actuar (Cagran, Schmidt & Brown, 2011;Martínez & Bilbao, 2008). La poca claridad frente al diagnóstico, así como el acompañamiento que se hace a los padres, resulta crucial para asumir la discapacidad en forma integral; al tener un diagnóstico fiable las familias logran albergar deseos positivos en relación con la discapacidad.…”
Section: Introductionunclassified